The Effects of Photovoltaic Panel’s Temperature Towards Photovoltaic Electrical Power Output - Mohd Salleh, Nor Izzati; Nor, Ahmad Fateh Mohamad; Jumaat, Siti Amely; Yahaya, Jabbar Al-Fattah; Zainal, Nurezayana (Journal of Quranic Sciences and Research, 2021)
Photovoltaic (PV) system is recognized as one of the most current renewable energy types in producing electrical power. However, one of the problems of PV systems is that the performance of PV panel output is dependent on the climate condition. Hence, it is important to predict the actual generating output power of PV systems. This study investigates the relationship between the temperature of the PV panel with the PV power output. The PV systems installed at the rooftop of Mega label SDN. BHD. with type of poly-crystalline 405.72KWP has been chosen as the reference system in this study. The results have shown that the rise of PV panel’s temperature will make the value of the PV electrical power output decreases.